2011
DOI: 10.1152/ajpheart.00388.2011
|View full text |Cite
|
Sign up to set email alerts
|

Early subclinical increase in pulmonary water content in athletes performing sustained heavy exercise at sea level: ultrasound lung comet-tail evidence

Abstract: Gemignani A, L=Abbate A. Early subclinical increase in pulmonary water content in athletes performing sustained heavy exercise at sea level: ultrasound lung comet-tail evidence. Am J Physiol Heart Circ Physiol 301: H2161-H2167, 2011. First published August 26, 2011; doi:10.1152/ajpheart.00388.2011.-Whether prolonged strenuous exercise performed by athletes at sea level can produce interstitial pulmonary edema is under debate. Chest sonography allows to estimate extravascular lung water, creating ultrasound lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…This extravascular fluid resolved by 12 h postevent (p<0.01) 21. These findings appear to support that extravascular fluid may appear after a long-distance triathlon, although in asymptomatic athletes the clinical relevance is uncertain.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…This extravascular fluid resolved by 12 h postevent (p<0.01) 21. These findings appear to support that extravascular fluid may appear after a long-distance triathlon, although in asymptomatic athletes the clinical relevance is uncertain.…”
Section: Resultssupporting
confidence: 55%
“…Finally, using a novel ultrasound technique to evaluate for extravascular lung water, Pingitore et al evaluated 31 ironman triathlon (2.4 mile swim, 112 mile bike, 26.2 mile run) competitors (29 males and 2 females), and found that immediately after the event, despite remaining asymptomatic, 23 of 31 athletes (74%) demonstrated evidence of increased extravascular fluid compared to only 2 athletes (6.4%) before the event (p<0.01) 21. This extravascular fluid resolved by 12 h postevent (p<0.01) 21.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used ultrasound to detect lung edema and reported the incidence of ultrasound lung comets. 13 None of the athletes had evidence of lung edema before the event, while 75% showed evidence of pulmonary edema immediately post-race, and 42% had persistent findings of pulmonary edema 12 hours post-race. Their data and several case reports [14][15][16] have demonstrated that extreme exercise can result in pulmonary edema and support the findings of West et al …”
Section: Exercise-induced Pulmonary Hemorrhagementioning
confidence: 85%
“…Evidence for pulmonary oedema has been shown in competitive rowers [28], during exertion in dry cold environments and in cases of emotional stress and sexual intercourse [29], in addition to long distance runners and triathletes [30][31][32][33][34][35][36][37][38][39][40] and competitive cyclists [41,42]. The importance of mild oedema in reducing exercise capacity has been questioned [43].…”
Section: Exercise-induced Pulmonary Oedemamentioning
confidence: 99%